The Development of Wordwall-Based Digital Media for Teaching English Vocabulary for Sixth Graders - Dewi, Ni Putu Anjar Astriani; Utami, I.G.A Lokita Purnamika; Suprianti, G.A.P (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims todevelop Wordwall-based digital media for Englishsubjects focusing on teaching vocabulary to support the material in the Merdeka Curriculum textbook